Biomechanics Energetics of Natural Assisted Human Comparative Movement Locomotion - Ardigo, Luca Paolo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Movement and locomotion have always been key activities for all animals, being related to the most crucial life functions: retrieving food, facing environmental issues and mating. Humans developed complex upper arms movements and bipedal gaits in order to move and locomote. To enhance their performance, they started inventing smart passive mechanical tools. This need arose from intrinsic limitations of their muscle-joint-bone systems and metabolic power availability. Newly invented devices were mainly introduced in order to cope with such constraints. The aim of this Special Issue is to advance knowledge regarding symmetry, biomechanics and energetics of passively assisted human movement and locomotion.